À espera de Lili: uma avaliação em profundidade da Política Nacional de Atenção às Mulheres em Situação de Privação de Liberdade e Egressas do Sistema Prisional (PNAMPE) no Instituto Penal Feminino do Ceará - Freitas, Nikaelly Lopes de (2023)
The consolidation of incarceration as the main tool for social control of unwanted populations has constituted a relevant instrument through which necropolitical extermination is manifested in capitalist societies, a project firmly structured by race, class and gender. In this context, prison has been established as an institution traditionally aimed at a male, young and marginalized population, being idealized and implemented based on androcentric structures, but from which women have never been exempt. With this, concern arises about the impact of prison on women, the treatment they receive and the meeting of their medical needs, mainly with regard to the promotion and attention to sexual and reproductive health. However, although imprisoned women have progressively gained space in scientific investigations in the last two decades, most of the work is linked to motherhood and based on the perspective of the child's best interest and child health, which is why the present research focused primarily on women's comprehensive health. In view of this, the objective was to evaluate in depth the National Policy for Attention to Women in Situations of Deprivation of Liberty and Those Leaving the Prison System in terms of health practices at the Instituto Penal Feminino Desembargadora Auri Moura Costa, in Ceará. To this end, the following specific objectives were established: a) Investigate how health practices are carried out in the Prison Unit studied, based on the perception of its actors; b) Analyze the content of the Policy in order to understand its conceptual bases and guiding paradigms; c) Describe the social, economic and political context of the Policy's formulation and trajectory. In pursuit of the proposed objectives, a qualitative approach was adopted using bibliographic and documentary research combined with field research, where ethnographically inspired participant observation was used at IPFDAMC and Creche Amadeu Barros Leal. In addition, open in-depth interviews and questionnaires were carried out, through which 19 women (inmates and ex-prisoners) were interviewed and information was collected from the prison administration and medical team. Aiming for an extensive, dense and multidimensional assessment, Lazar's (2007) Feminist Critical Discourse Analysis (ACFD) was used to analyze the collected data, covering the four axes of In-Depth Assessment (Rodrigues, 2008). It was found that imprisoned women live in the light of motherhood or in the shadow of invisibility, being subjected to cruel and degrading treatments intensified by gender violence. As a result, the physical, emotional and psychological marks point to the imposition of a life sentence, both from a social and biological point of view. It was concluded that imprisonment is preceded by a series of extrajudicial sanctions to which women are subjected, in a context of marked inequality in which prison is used as public policy. In this scenario, women continue to be disproportionately affected by prison and unworthy of the problems caused by it, within a social structure of imposing poverty, being faced within the scope of public policies. Therefore, the work presents contributions to the study of female prison health and the permanent impact of prison on the physical, mental and social well-being of women prisoners and their communities.